Current Obesity Reports - Kushner, Robert; Dixon, John B.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal aims to offer expert review articles on the most significant recent developments in the interdisciplinary field of obesity research. By providing clear, insightful, balanced contributions, the journal intends to serve all those involved in the treatment and prevention of obesity and the related spectrum of cardiovascular, endocrinological, gynecological, oncological, psychological, respiratory, and rheumatological conditions. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas across the field. Section Editors select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An Editorial Board of more than 25 internationally diverse members reviews the annual table of contents, ensures that topics include emerging research, and suggests topics of special importance to their country/region. We also provide commentaries from well-known figures in the field.
Keywords: Medicine; Cardiology; Diabetes; Endocrinology; Metabolic diseases; Behavioral therapy; Endocrinology; Medicine/Public Health, general; Metabolic Diseases; Diabetes; Cardiology; Behavioral Therapy